FORENSIC MEDICAL ASSESSMENT OF MORPHOFUNCTIONAL CHANGES IN THE LIVER IN CLOSED WOUNDS OF THE ABDOMINAL CAVITY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Promising in solving the forensic medical determination of the circumstances of blunt trauma (type of impact, direction, force and area of the traumatic surface) based on the morphology of liver injuries is an in-depth study of the issues of the formation mechanism and the establishment of the morphological characteristics of local and distant liver injuries. The location and severity of liver injuries provide valuable information about the conditions of blunt abdominal trauma. The search for morphological equivalents of the processes of compression, stretching and shear in liver injuries seems important for solving forensic issues.